Invasive Mammary Paget’s Disease Without Underlying Malignancy: A Case Report - Citra Kalisa, Raja Eka; Ennesta Asri; Indah Indria Sari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Mammary Paget's disease (MPD) with skin invasion is a rare condition that is often associated with an underlying malignancy. However, invasive MPD without malignancy is even rarer and often misdiagnosed. Case presentation: This report presents the case of a 56-year-old woman who presented with a progressively enlarging scaly erythematous plaque on her left nipple for 6 months. Dermoscopy and histopathological examination confirmed the diagnosis of invasive MPD, but radiological examination did not reveal any malignancy. Conclusion: Invasive MPD without malignancy is a rare but important entity to recognize. Awareness of this condition can help prevent overdiagnosis and unnecessary treatment.